Analysis and design of nickel-based single crystal superalloys - Zhu, Z (2014)
This thesis provides a research into properties of nickel-based single crystal super- alloys. The underlying quantitative relationship between alloy chemistry and the important properties have been studied. To design new grade of single crystal su- peralloys, computational modelling methods have been proposed which build on the findings of composition-microstructure-property relationships. A physical model for the creep deformation of single crystal superalloys is presented, in which the dependence of the kinetics of creep deformation on alloy chemistry is rationalised. The rate-controlling step is considered to be climb of dislocations at the matrix/particle interfaces and their rate of escape from trapped configurations. The effects of microstructural scale precipitate size, geometry and spacing are also studied. A first order estimate for the rate of creep deformation emerges from the model, which is useful for the purposes of alloy design. Three new single crystal superalloys have been isolated using theory-based com- putational modelling approaches, termed Alloys-By-Design methods. They are (i) an oxidation-resistant low Re-containing alloy with balanced properties, intended for general-purpose gas turbine applications; (ii) an alloy containing 5.6 wt.% Re and 2.6 wt.% Ru suitable for high performance jet engine applications, and (iii) a cheap, corrosion-resistant alloy for power generation applications. The new alloys have been manufactured using investment casting techniques, and their creep and oxidation behaviour evaluated. The multicomponent composition space pertinent to the single crystal nickel-based superalloys has been mapped and searched, by using newly developed numerical al- gorithms. This allowed compositions of alloys conferring the microstructures needed for optimal properties to be identified, at a resolution of 0.1 wt.%. Databases have been constructed which contain all appropriate compositions available in these systems. When coupled with composition- and microstructure-dependent property models, the databases can be searched to identify new alloys predicted to exhibit the very best properties or combinations of them.